2015
DOI: 10.1186/s13287-015-0036-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of a simple procedure for the treatment of femoral head osteonecrosis with intra-osseous injection of bone marrow mesenchymal stromal cells: study of their biodistribution in the early time points after injection

Abstract: IntroductionOsteonecrosis of the femoral head (ONFH) is a degenerative disease progressing to a femoral head (FH) collapse. Injection of osteoprogenitor cells like bone marrow mesenchymal stromal cells (BMSCs) into the FH appears to be a good therapeutic treatment. However, safety and efficacy of BMSCs to treat bone defect are the main preclinical data required for clinical application. Efficacy and the lack of risk of cell transformation after amplification of BMSCs have been extensively described. The main o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 46 publications
3
29
0
6
Order By: Relevance
“…One of the main causes of SANFH is the stagnation of osteoblast differentiation and osteopenia [33], so regulating this process has profound significance for SANFH treatment. BMSCs are important stromal cells in osteogenesis and metabolism [34].…”
Section: Discussionmentioning
confidence: 99%
“…One of the main causes of SANFH is the stagnation of osteoblast differentiation and osteopenia [33], so regulating this process has profound significance for SANFH treatment. BMSCs are important stromal cells in osteogenesis and metabolism [34].…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed that repeated administration of PRP (10 ml per week) relieved the pathogenesis of knee osteoarthritis. A previous report indicated that inflammatory cytokines form a complex regulatory signal network in osteonecrosis of the femoral head that is mediated by various intracellular kinase signaling pathways to regulate recruitment, stimulation and activation of autoimmune cells (31). Although the causes of knee osteoarthritis are not fully understood, laboratory and clinical evidence has suggested that inflammatory cytokines may contribute to its pathogenesis (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded, however, that the more reliable osteonecrosis level seen in their liquid nitrogen treated group made cryo-injury more suitable for the research of standardized treatment of existing ONFH. In the treatment of ONFH, Lebouvier et al [81] found treatment of a natural pig ONFH by autologous BMSCs indicated a beginning of bone healing as early as two weeks with a complete healing after nine weeks. None of the above models have shown the reproducibility demonstrated by small mammal, chicken, and emu models of SONFH.…”
Section: Other Animal Modelsmentioning
confidence: 99%